Current Practices in Growth Chart Utilization among Healthcare Practitioners in Saudi Arabia: A Cross-Sectional Study - Abeer M. Aljaadi; Rana H. Mosli; Ruba H. Eid; Dania H. Bin-Ali; Essra A. Noorwali; Reem O. Basaqr; Hala Al-Otaibi (International Journal of Clinical Practice)
Growth charts (GCs) are essential tools for monitoring children’s growth and overall health status. The extent to which healthcare professionals in Saudi Arabia (SA) use national and international GC, and adhere to standardized practices remains unclear. This study aimed to investigate current GC practices among healthcare practitioners in SA. A cross-sectional study was conducted on 193 healthcare practitioners in SA who completed an online questionnaire that assessed their characteristics and practices related to the use of GC. Descriptive, bivariate, and logistic regression analyses were performed. Participants reported using different GCs during the assessments, with the following distribution: GC of the Centers for Disease Control and Prevention (CDC) (24%), GC of the World Health Organization (WHO) (22%), Saudi GC (21%), and more than one type of GC (30%). Among the participants, 62% recorded GC data for both sick and well child, and 72.5% used GC with new and follow-up children. Only 56% reported discussing the GC output with patients or parents. Adjusting for covariates, dietitians were more likely to use GC with new and follow-up patients (odds ratio (OR): 2.61, 95% confidence interval (CI): 1.13, 6.02) and regularly discuss GC output with patients/parents (OR: 2.65, 95% CI: 1.29, 5.43) compared to other healthcare practitioners. Our findings showed significant variability in the use of GC among healthcare professionals in SA. The limited adoption of Saudi GC warrants further investigation to address practice obstacles and monitor children’s growth.